2015
DOI: 10.1016/j.envres.2015.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indoor nitrogen dioxide on lung function in urban environment

Abstract: a b s t r a c tBackground: High levels of indoor NO 2 are associated with increased asthma symptoms and decreased expiratory peak flows in children. We investigated the association of exposure to domestic indoor NO 2 , objectively measured in winter and spring, with respiratory symptoms and lung function in a sample of adolescents from a southern Mediterranean area. Methods: From a large school population sample (n ¼2150) participating in an epidemiological survey in the urban area of the City of Palermo (sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…[23][24][25] School indoor environments frequently present poor IAQ due to high indoor CO 2 concentration: This is associated with decrease in annual average daily attendance 26 and students' performance. [23][24][25] School indoor environments frequently present poor IAQ due to high indoor CO 2 concentration: This is associated with decrease in annual average daily attendance 26 and students' performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] School indoor environments frequently present poor IAQ due to high indoor CO 2 concentration: This is associated with decrease in annual average daily attendance 26 and students' performance. [23][24][25] School indoor environments frequently present poor IAQ due to high indoor CO 2 concentration: This is associated with decrease in annual average daily attendance 26 and students' performance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several factors such as poor buildings quality, lack of hygiene procedures, and insufficient ventilation (natural and/or mechanical) may worsen schoolchildren's exposure to indoor pollutants. [23][24][25] School indoor environments frequently present poor IAQ due to high indoor CO 2 concentration: This is associated with decrease in annual average daily attendance 26 and students' performance. 27,28 In addition, biological agents, such as endotoxins and dust mite allergens (Dermatophagoides pteronyssinus-Der p 1), can significantly affect the air quality in school environments.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen dioxide is an urban air pollutant whose emissions in outdoor air are mainly caused by road traffic, power plants, and industrial processes, while combustion appliances such as gas stoves and heaters as well as vented appliances with defective installations are the principal indoor sources that may generate very high concentrations of nitrogen dioxide and thus contribute importantly to personal exposure (Chaloulakou et al 2008;Dennekamp et al 2001;Lewné et al 2004). Some researchers have found that the use of gas stoves with poor ventilation is the dominant activity influencing indoor concentration of nitrogen dioxide and increasing the risk of adverse health effects (Belanger et al 2006;Cibella et al 2015;Willers et al 2006). The relationship between exposure to nitrogen dioxide and health effects has been confirmed in a number of epidemiological studies.…”
Section: Introductionmentioning
confidence: 91%
“…9 (Challoner and Gill, 2014;Cibella et al, 2015;Xie et al, 2015), and high levels of NO 2 are associated with increased respiratory symptoms and reduced lung function (Cibella et al, 2015;Kattan et al, 2007). Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 98%